1979
DOI: 10.4315/0362-028x-42.7.569
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hafnia alvei and a Lactobacillus Species in the Spoilage of Vacuum-Packaged Strip Loin Steaks

Abstract: A microbiological examination of vacuum-packaged strip loin steaks that were defective (gassy packages, hydrogen sulfide odor) revealed high total counts (107–108/cm2) with Hafnia alvei, Lactobacillus and Pseudomonas spp. as major isolates. Re-inoculation experiments indicated that H. alvei was the likely cause of the hydrogen sulfide odor. Gas formation resulted from the activity of heterofermentative lactobacilli and H. alvei. Improvements in plant practices and temperature control eliminated the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
7

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 0 publications
1
31
0
7
Order By: Relevance
“…, 2011). Although in a lesser extent, members of the Enterobacteriaceae family have also been described as potential causative agents of ‘blown pack’ spoilage (Hanna et al. , 1979; Brightwell et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2011). Although in a lesser extent, members of the Enterobacteriaceae family have also been described as potential causative agents of ‘blown pack’ spoilage (Hanna et al. , 1979; Brightwell et al.…”
Section: Introductionmentioning
confidence: 99%
“…1989). In the past, this type of spoilage was commonly associated with vacuum‐packed meat stored at an abused temperature, in which spoilage bacteria such as Serratia liquefaciens , Enterobacter aerogenes or Hafnia alvei grow and produce gas to cause “blown pack” spoilage (Hanna et al. 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have reported the development of such odors in meats as bacterial numbers increase during storage. More specifically, the odors have been described as "sour," "buttermilk," " sulfur-like," and "hydrogen sulfide" (Hanna et al, 1979(Hanna et al, , 1983Vanderzant et al, 1986). Edwards and Dainty (1987) examined the microbial flora and volatile compounds found on normal and high pH pork which was vacuum-packaged and stored at 5°C.…”
Section: Introductionmentioning
confidence: 99%